Shades of microRNAs: new biomarkers in acute ischemic stroke? - Preissner, Klaus T. (Non-coding RNA Investigation, 2017)
AIS is a thrombotic syndrome, which is the result of a reduced or an interrupted blood flow to the brain, culminating in cell death, whereby approx two million neurons and 14 billion synapses are lost during each minute of stroke. According to the World Health Organization, 15 million people worldwide suffer stroke each year, and of these, 5 million die and another 5 million are permanently disabled as a result. Thus, stroke is the leading cause of long-term disability and ranks second after ischemic heart disease as a cause of death worldwide. Although the incidence of stroke is on the decline in developed countries, largely due to efforts to lower blood pressure and reduce smoking, the overall rate of stroke is increasing exponentially due to an ever-aging population (1).